Increase in choroidal thickness after blue light stimulation of the blind spot in young adults - Hoseini-Yazdi, Hosein; Read, Scott A.; Collins, Michael J.; Bahmani, Hamed; Ellrich, Jens; Schilling, Tim (Bioelectronic Medicine, 2024)
Background: Blue light activates melanopsin, a photopigment that is expressed in intrinsically photosensitive retinal ganglion cells (ipRGCs). The axons of ipRGCs converge on the optic disc, which corresponds to the physiological blind spot in the visual field. Thus, a blue light stimulus aligned with the blind spot captures the ipRGCs axons at the optic disc. This study examined the potential changes in choroidal thickness and axial length associated with blue light stimulation of melanopsin-expressing ipRGCs at the blind spot. It was hypothesized that blue light stimulation at the blind spot in adults increases choroidal thickness. Methods: The blind spots of both eyes of 10 emmetropes and 10 myopes, with a mean age of 28 ± 6 years (SD), were stimulated locally for 1-minute with blue flickering light with a 460 nm peak wavelength. Measurements of choroidal thickness and axial length were collected from the left eye before stimulation and over a 60-minute poststimulation period. At a similar time of day, choroidal thickness and axial length were measured under sham control condition in all participants, while a subset of 3 emmetropes and 3 myopes were measured after 1-minute of red flickering light stimulation of the blind spot with a peak wavelength of 620 nm. Linear mixed model analyses were performed to examine the light-induced changes in choroidal thickness and axial length over time and between refractive groups. Results: Compared with sham control (2 ± 1 μm, n = 20) and red light (−1 ± 2 μm, n = 6) stimulation, subfoveal choroidal thickness increased within 60 min after blue light stimulation of the blind spot (7 ± 1 μm, n = 20; main effect of light, p < 0.001). Significant choroidal thickening after blue light stimulation occurred in emmetropes (10 ± 2 μm, p < 0.001) but not in myopes (4 ± 2 μm, p > 0.05). Choroidal thickening after blue light stimulation was greater in the fovea, diminishing in the parafoveal and perifoveal regions. There was no significant main effect of light, or light by refractive error interaction on the axial length after blind spot stimulation. Conclusions: These findings demonstrate that stimulating melanopsin-expressing axons of ipRGCs at the blind spot with blue light increases choroidal thickness in young adults. This has potential implications for regulating eye growth.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Axial length; Intrinsically photosensitive retinal ganglion cell; Melanopsin; Myopia; Optic disc